Donor–Donor′–Acceptor Triads Based on [3.3]Paracyclophane with a 1, 4‐Dithiafulvene Donor and a Cyanomethylene Acceptor: Synthesis, Structure, and Electrochemical and Photophysical Properties. Issue 44 (6th July 2018) - Sako, Katsuya; Hasegawa, Tomoya; Onda, Hiroyuki; Shiotsuka, Michito; Watanabe, Motonori; Shinmyozu, Teruo; Tojo, Sachiko; Fujitsuka, Mamoru; Majima, Tetsuro; Hirao, Yasukazu; Kubo, Takashi; Iwanaga, Tetsuo; et al.
Abstract: Donor–donor′–acceptor triads (1, 2 ), based on [3.3]paracyclophane ([3.3]PCP) as a bridge, with electron‐donating properties (D′) using 1, 4‐dithiafulvene (DTF; TTF half unit) as a donor and dicyanomethylene (DCM; TCNE half unit) or an ethoxycarbonyl‐cyanomethylene (ECM) as an acceptor were designed and synthesized. The pulse radiolysis study of1 a in 1, 2‐dichloroethane allowed the clear assignment of the absorption bands of the DTF radical cation (1 a .+ ), whereas the absorption bands due to the DCM radical anion could not be observed by γ‐ray radiolysis in 2‐methyltetrahydrofuran rigid glass at 77 K. Electrochemical oxidation of1 a first generates the DTF radical cation (1 a .+ ), the absorption bands of which are in agreement with those observed by a pulse radiolysis study, followed by dication (1 a 2+ ). The ESR spectrum of1 a .+ showed a symmetrical signal with fine structure and an ESR simulation predicted that the spin of1 a .+ is delocalized over S and C atoms of the DTF moiety and the central C atom of the trimethylene bridge bearing the DTF moiety. Pulse radiolysis, ESR, and electrochemical studies indicate that the DTF radical cation of1 a .+ is more stable than that of6 .+, and the latter shows a strong tendency to dimerize. This result indicates that the [3.3]PCP moiety as a bridge can stabilize the DTF radical cation more than the 1, 3‐diphenylpropane moiety because of kinetic stability due to its rigid structure and the weak electronic interaction of DTF and DCM moieties through [3.3]PCP. Abstract : Triangular relationship : DTF(D)–[3.3]PCP(D′)–DCM or ECM (1, 2 ) triads, based on [3.3]paracyclophane ([3.3]PCP) as a bridge, with electron‐donating properties (D′) using 1, 4‐dithiafulvene (DTF) as a donor and dicyanomethylene (DCM) or an ethoxycarbonylcyanomethylene (ECM) as an acceptor were synthesized.